Improving Students' Vocabulary by Using Manga - Ahmad Nofrian; Syafryadin, Syafryadin; Sujarwati, Iis (Edu-Ling: Journal of English Education and Linguistics, 2023)
A vocabulary is a collection of words that have meaning and are used in sentences. Manga is a kind of medium that the teacher can use to teach vocabulary. Manga contains vocabulary that relates to the images, which can help students understand new vocabulary more quickly. The descriptive-qualitative research approach was applied in this study. The participants of this study were 16 eighth grade students from SMPN 4 Pendopo Barat in the academic year 2023-2024. To obtain data, the researcher employed a vocabulary test, observation, field notes, and interview. According to the results, there was a significant increase in students' ability in the form of an increase in English vocabulary and also in their motivation to understand the vocabulary contained in the manga. Additionally, the researcher saw several factors that influenced the improvement of students' vocabulary comprehension by using the media in the form of manga. The factors that led to the improvement of students' vocabulary by using manga were students' motivation and students’ activeness in the learning process. The researcher noticed that students became more enthusiastic and excited during the teaching and learning process by applying this medium. Therefore, the researcher suggests that English teachers can use manga, especially in order to improve vocabulary as well as students' interest in reading.